2019
DOI: 10.3892/mmr.2019.10645
|View full text |Cite
|
Sign up to set email alerts
|

Suppression of microRNA‑27a protects against liver ischemia/reperfusion injury by targeting PPARγ and inhibiting endoplasmic reticulum stress

Abstract: liver ischemia-reperfusion (i/r) injury is an important clinical issue related to liver transplantation. recent studies suggest that micrornas are implicated in various biological and pathological processes, including liver i/r injury. This study aimed to investigate the role and potential mechanism of mir-27a during liver i/r injury. a liver i/r model was induced via 60 min of ischemia and reperfusion for 6 h in rats. cells were transfected with mir-27a mimics or the mir-27a inhibitor to examine the effect of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…They can affect apoptosis, autophagy, inflammation, oxidation, etc . By bioinformatic analysis and a dual-luciferase reporter assay, PPARγ was identified as a target gene of miR-27a ( Chi et al, 2019 ). For the molecular mechanism of PPARγ signaling, microRNA, or other noncoding RNA (circular RNA, long noncoding RNA, etc .…”
Section: Summary and Perspectivementioning
confidence: 99%
“…They can affect apoptosis, autophagy, inflammation, oxidation, etc . By bioinformatic analysis and a dual-luciferase reporter assay, PPARγ was identified as a target gene of miR-27a ( Chi et al, 2019 ). For the molecular mechanism of PPARγ signaling, microRNA, or other noncoding RNA (circular RNA, long noncoding RNA, etc .…”
Section: Summary and Perspectivementioning
confidence: 99%
“…However, modulation of ATAD3a expression has little effect on the activation of caspases, which demonstrated that the regulation of apoptosis by ATAD3a occurs in a caspase-independent manner. It has been documented that miR-27a plays an important role in the regulation of apoptosis [42][43][44]. miR-27a can regulate cell apoptosis by targeting Fas-associated protein with death domain (FADD) [42], SMAD5 [43], PPAR gamma [44], etc.…”
Section: Discussionmentioning
confidence: 99%
“…endoplasmic reticulum stress (erS) is considered a driving force of acute renal failure (arF) induced by i/r (9). increasing evidence indicates that persistent activation of erS and subsequent elevation of apoptotic cascades are key to the pathogenesis of renal i/r injury (10)(11)(12)(13). additionally, a previous study confirmed that apoptosis occurs in the early phase of ischemia and can be worsened by reperfusion (13).…”
Section: Introductionmentioning
confidence: 98%